2020
DOI: 10.2147/jpr.s258433
|View full text |Cite
|
Sign up to set email alerts
|

<p>CBD Effects on TRPV1 Signaling Pathways in Cultured DRG Neurons</p>

Abstract: Introduction Cannabidiol (CBD) is reported to produce pain relief, but the clinically relevant cellular and molecular mechanisms remain uncertain. The TRPV1 receptor integrates noxious stimuli and plays a key role in pain signaling. Hence, we conducted in vitro studies, to elucidate the efficacy and mechanisms of CBD for inhibiting neuronal hypersensitivity in cultured rat sensory neurons, following activation of TRPV1. Methods Adult rat dorsal root ganglion (DRG) neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 50 publications
2
29
0
3
Order By: Relevance
“…Accordingly, the anticonvulsant effects of CBD were reversed by a Trpv1 antagonist in the PTZ model (Vilela et al, 2017) and reduced in Trpv1 −/− mice compared to wildtype mice in the MES model (Gray et al, 2020). These results are consistent with cellular studies which show that CBD activates and subsequently desensitizes Trpv1 receptors (De Petrocellis et al, 2011;Iannotti et al, 2014;Anand et al, 2020).…”
Section: Introductionsupporting
confidence: 84%
“…Accordingly, the anticonvulsant effects of CBD were reversed by a Trpv1 antagonist in the PTZ model (Vilela et al, 2017) and reduced in Trpv1 −/− mice compared to wildtype mice in the MES model (Gray et al, 2020). These results are consistent with cellular studies which show that CBD activates and subsequently desensitizes Trpv1 receptors (De Petrocellis et al, 2011;Iannotti et al, 2014;Anand et al, 2020).…”
Section: Introductionsupporting
confidence: 84%
“…A recent study, examining the effects of CBD on capsaicin response in rat DRG neurons, found that administration of 10 μM and 50 μM CBD caused significant calcium influx, but lower concentrations did not. 36 In this study, 50 μM CBD was the most effective concentration, in a similar range to CBG (30 μM). Various other receptor targets for CBD have been identified, such as the orphan G-protein coupled receptor GPR18, GPR55, PPARs, 5-HT1a and the α3 and α1 glycine receptors.…”
Section: Discussionsupporting
confidence: 53%
“…Cannabinoid agonists were previously reported to stimulate TRPV1 and TRPA1 in sensory neurons, leading to calcium influx and desensitization. 35 We have recently reported CBD inhibition of TRPV1 in DRG neurons at low physiological doses that did not stimulate calcium influx, 36 similar to inhibition of TRPV1 and TRPM8 in transfected HEK cells. 27 However, as higher concentrations of cannabinoids induce calcium influx, it is likely that these doses of CBG, CBD and THC would lead to desensitization of TRPV1 in DRG neurons, similar to capsaicin-mediated effects.…”
Section: Introductionmentioning
confidence: 77%
“…From a mechanistic point of view, it should be noted that acrosome reaction in mammals is strictly dependent on the upstream activation of the cAMP/PKA system [ 40 ]. On the other hand, the cAMP/PKA system has recently been involved in the upstream phosphorylation of TRPV1, which is associated with the sensitization of the receptor to activation stimuli [ 41 ]. Our results are consistent with this sequential order of cell events and allow us to tentatively exclude a major role of sperm capacitation on the effect exerted by Chol loss on TRPV1-mediated function.…”
Section: Discussionmentioning
confidence: 99%